Variasi Molaritas Naoh Dan Alkali Aktivator Beton Geopolimer - Mira Setiawati; Sri Martini; Rully Nurulita (Jurnal Deformasi, 2022)
Cement as a building material for concrete produces CO2 which can damage the earth's atmosphere. Therefore, environmentally friendly geopolymer concrete is the choice. The main ingredients for making this concrete are pozzolanic materials which are rich in Silica (SiO3) and Alumina (Al2O3) as a substitute for cement and alkali activator in the form of Sodium Hydroxide (NaOH) and (Na2SiO3) as binders.This study aims to determine the variation of the mixture for the highest compressive strength. The ratio of fly ash type F and alkali activator is 74%:26%. The molarity of NaOH used was 10M, 12M, 14M, the ratio of Na2SiO3 and NaOH was 2.5:1; 3.0:1; 3.5:1. The test object is cylindrical size 15cm x 30cm and the compressive strength test is 28 days old.The test results with the ratio of NaOH and Na2SiO3 2.5:1 at 10M, 12M, 14M NaOH are 25.81 Mpa, 27.00 MPa, 28.98 MPa. While the compressive characteristics are 24.32 Mpa, 24.67 Mpa, 26.58 Mpa. The test results show that the ratio of molarity and alkali activator greatly affects the compressive strength and workability of geopolymer concrete. High molarity will produce high compressive strength. Meanwhile, the higher the alkali activator ratio, the lower the compressive strength produced.Â